2009
DOI: 10.1371/journal.ppat.1000433
|View full text |Cite
|
Sign up to set email alerts
|

Broadly Neutralizing Human Anti-HIV Antibody 2G12 Is Effective in Protection against Mucosal SHIV Challenge Even at Low Serum Neutralizing Titers

Abstract: Developing an immunogen that elicits broadly neutralizing antibodies (bNAbs) is an elusive but important goal of HIV vaccine research, especially after the recent failure of the leading T cell based HIV vaccine in human efficacy trials. Even if such an immunogen can be developed, most animal model studies indicate that high serum neutralizing concentrations of bNAbs are required to provide significant benefit in typical protection experiments. One possible exception is provided by the anti-glycan bNAb 2G12, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
387
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 471 publications
(400 citation statements)
references
References 53 publications
12
387
1
Order By: Relevance
“…This view has been reinforced by recent studies showing that HIV-1 infection can be limited or even prevented in animals with a wide range of functional antibody titers as measured by in vitro neutralization assays when these antibodies are continuously present, as would be the case for vaccine-induced immunity (31,37,38).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This view has been reinforced by recent studies showing that HIV-1 infection can be limited or even prevented in animals with a wide range of functional antibody titers as measured by in vitro neutralization assays when these antibodies are continuously present, as would be the case for vaccine-induced immunity (31,37,38).…”
Section: Discussionmentioning
confidence: 97%
“…The higher neutralizing IC 50 titers obtained with HXB2-V570A in purified IgG from sera of animals immunized with either (CCIZN36) 3 or (CCIPN36) 3 suggested that neutralization responses should be detectable in unfractionated serum. To gain preliminary insight on the breadth of the neutralization response, we tested individual guinea pig serum samples from these groups against a small panel of HIV-1 isolates as well as simian HIV (SHIV) SF162p3, which has previously been tested in multiple monkey challenge studies (29)(30)(31). The HIV-1 viruses used for this panel are representative of tier 1 isolates, defined as being sensitive to antibody-mediated neutralization and mainly comprising T celladapted viruses (32).…”
Section: Serological Analysis Of Animals Immunized With Nhr Peptidementioning
confidence: 99%
“…2 L and M), slow neutralization mechanisms leave a window of opportunity for virus escape. Whereas previous studies using passively transferred NMAbs suggest that 2G12 may be more inhibitory than MPER NMAbs in vivo (32,40), both b12 and 2G12 are highly protective (31,40,41). Further studies will be needed to learn whether information concerning NAb neutralization mechanisms and kinetics can be used to advance the HIV-1 vaccine effort.…”
Section: G12 Inhibits Cd4 and Ccr5 Binding And Blocks A Coreceptordementioning
confidence: 95%
“…On the basis of this evidence, we tested the possibility that NAbs might function by slowing HIV-1 entry. We initially used NMAb 2G12, which binds to N-glycans with α (1, 2)-linked mannose termini at positions N295, N332, and N392 near the V3 loop in the "glycan shield" region of gp120 (1,29,30), because 2G12 strongly inhibits HIV-1 and SHIV in vivo (1,31,32). We report that 2G12 functions by this kinetic mechanism.…”
mentioning
confidence: 98%
“…Several broadly neutralizing antibodies (bNAbs) to HIV-1 gp160 have been isolated, including a group that binds to gp120 (10)(11)(12)(13)(14)(15)(16)(17)(18) and a group that is specific for gp41 (19)(20)(21). Importantly, passive transfer of bNAbs to monkeys effectively protects them against simian-human immunodeficiency virus infection (22)(23)(24)(25)(26)(27)(28)(29)(30)(31), and it has therefore been proposed that vaccines that elicit such antibodies may be protective against infection in humans (1,2,(32)(33)(34).…”
mentioning
confidence: 99%